Understanding the World Through Systems: History, Classification and Future Directions (London Journal of Engineering Research, 2025)
In recent years, the concept of "system" has been increasingly used. As a result, the concept of a system is found in almost all fields of knowledge, which has given rise to many definitions. It is almost impossible to give an accurate comprehensive definition of the system. Any of them will be relative.Therefore, it is better to consider the historical process of the formation of the concept of "system".
Keywords: Fuzzy controller; PID controller; two-wheeled balance robot; Continuous plane curve; Minimum one-sided Hausdorff distance; Exact algorithm; Comparison of computational efficiency; Roundness error evaluation.